Blood–Brain Barrier, Cell Junctions, and Tumor Microenvironment in Brain Metastases, the Biological Prospects and Dilemma in Therapies - Guan, Zhiyuan; Lan, Hongyu; Cai, Xin; Zhang, Yichi; Liang, Annan; Li, Jin (Frontiers in Cell and Developmental Biology, 2021)
Brain metastasis is the most commonly seen brain malignancy, frequently originating from lung cancer, breast cancer, and melanoma. Brain tumor has its unique cell types, anatomical structures, metabolic constraints, and immune environment, which namely the tumor microenvironment (TME). It has been discovered that the tumor microenvironment can regulate the progression, metastasis of primary tumors, and response to the treatment through the particular cellular and non-cellular components. Brain metastasis tumor cells that penetrate the brain–blood barrier and blood–cerebrospinal fluid barrier to alter the function of cell junctions would lead to different tumor microenvironments. Emerging evidence implies that these tumor microenvironment components would be involved in mechanisms of immune activation, tumor hypoxia, antiangiogenesis, etc. Researchers have applied various therapeutic strategies to inhibit brain metastasis, such as the combination of brain radiotherapy, immune checkpoint inhibitors, and monoclonal antibodies. Unfortunately, they hardly access effective treatment. Meanwhile, most clinical trials of target therapy patients with brain metastasis are always excluded. In this review, we summarized the clinical treatment of brain metastasis in recent years, as well as their influence and mechanisms underlying the differences between the composition of tumor microenvironments in the primary tumor and brain metastasis. We also look forward into the feasibility and superiority of tumor microenvironment-targeted therapies in the future, which may help to improve the strategy of brain metastasis treatment.